Pedagogical Aspects Of Implementing Subject Integration In Primary Education (Global Scientific Review, 2025)
This article describes the content, essence of planning and organizing integrated lessons in primary education, the problems that teachers may encounter in the process of integrated education, and ways to overcome them. The pedagogical and psychological aspect of organizing integrated education in the development of students' mental processes and its importance at different age levels, as well as the organization of the use of game technologies, are discussed.